Quest for the Historical Thomas Apostle of India - Thonippara, Francis (Asian Horizons, 2009)
George Nedungatt , S.J., Quest for the Historical Thomas Apostle of India, Bangalore, Theological Publications in India, 2008, pp.xxxiv+428, price Rs.200.